Mobile Dispensary Seva: Helping Pune Fight the Pandemic - Bharatiya Jain Sangathana (My University, 2021)
This case study documents the impact of Mobile Dispensary Seva, a COVID-19 mitigation programme implemented in collaboration with Pune Municipal Corporation in Pune and Pimpri-Chindward, then one of the largest COVID-19 hotspots in the country. The programme was implemented in a phased manner across 4 states responding to the emerging challenges as the pandemic progressed. The components of programme includes Mobile Dispensary Seva, Mission Zero, Corona Se Do Haath, Prachar Rath and Smart Helmets. Mobile Dispensary Seva was implemented in Pune and its impact has been analyzed in this case study. Tempo travellers and school buses were converted into mobile dispensaries with a doctor, medical attendant and a volunteer stocked with clinic equipment and medicines to treat general ailments. Overall the programme led to early detection, isolation and breaking the chain of virus transmission resulting in reduced death ratio. Some of the specific outcomes of the programme includes detecting 808 COVID-19 positive case through screening of 6.4 lakh people, referring 8,880 suspected cases, specific focus on hotspots like slum clusters helped early identification of cases and reduce Case Fatality Ratio (CFR) and flatten the curve. The case study highlights the exemplary work of the field teams to encourage suspected people to go for swab testing and isolation to make the programme succeed.
Case Study as part of Stories of Change Series
Keywords: Emergency Health Response for COVID-19 Mitigation